The Economic Feasibility of Achieving SDG 6 (Clean Water and Sanitation) with Innovative Approach to Addressing Water Scarcity in Conflict Zones: Gaza Strip Study Case - Puspita Nurlilasari; Devi Maulida Rahmah; Roni Kastaman; Efri Mardawati; Januardi (PT SOLUSI EDUKASI BERDIKARI, 2024)
This study examines an innovative approach to achieving Sustainable Development Goal (SDG) 6 in conflict zones, using Gaza as a case study. Through an analysis of technological innovations, nature-based solutions, and an economic sustainability framework, we demonstrate how the challenges of water scarcity can be addressed amidst the constraints imposed by conflict. This research presents evidence-based recommendations for achieving universal access to clean water and sanitation, while ensuring economic feasibility in conflict-affected areas.